Fe-Zn double-metal cyanide complexes as novel, solid transesteritication catalysts - Srivastava, R.; Srinivas, D.; Ratnasamy, P. (Journal of Catalysis, 2006)
Fe-Zn double-metal cyanide complexes are currently used as catalysts for the ring-opening polymerization of epoxides, as well as the coupling of epoxides and CO2 for the production of polycarbonates. We report their novel application as highly efficient solid catalysts for the transesterification reactions of carbonates. The catalysts were prepared from aqueous solutions of ZnCl2 and K4Fe(CN)(6) in the presence of tert-butanol (complexing agent) and tri-block copolymer EO20PO70EO20 (average molecular weight, 5800; co-complexing agent). They were characterized by chemical analysis, XRD, thermal analysis, N-2 adsorption, magnetic susceptibility, SEM, and FTIR, diffuse reflectance UV-visible, EPR, and X-ray photoelectron spectroscopies. Their acidity was determined from the IR spectra of adsorbed pyridine and the temperature-programmed desorption of NH3. Catalyst samples prepared with both complexing and co-complexing agents were found to be more acidic and catalytically active than those prepared without these agents. These catalysts are more active/selective than other solid catalysts hitherto reported. Dimethyl carbonate, for example, could be synthesized with 100% selectivity and an isolated yield of >86% by the reaction of propene carbonate with methanol. The catalysts can be recycled without significant loss in activity. Lewis acidic Zn ions are the possible active sites for the transesterification reaction. (c) 2006 Published by Elsevier Inc.
Keywords: cyclic carbonate; Dimethyl carbonate; double metal cyanide Fe-Zn complexes; organic carbonate; transesterification catalyst